Rethinking decongestive lymphoedema treatment during the pandemic. (1st April 2021) - Everett, Jeanne; Lawrance, Sue; Phillips, Natalie
Abstract : During the course of the COVID-19 pandemic, lymphoedema and community clinicians have had to modify how they implement intensive treatments for patients with lymphoedema and chronic oedema. Using novel approaches to treat and move patients towards self-management regimes has enabled patients to be in control of their condition, particularly if they are unable to attend normal clinic appointments. This article explores how using Haddenham easywrap instead of time- and resource-intensive bandaging regimes, alongside the Haddenham LymphFlow Advance, as part of self-management programmes, can benefit patients' quality of life, reduce costs and resource use and enable patients to self-manage this long-term chronic condition more effectively.